2016
DOI: 10.1038/srep21124
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome analysis among parental inbred and crosses reveals the role of dominance gene expression in heterosis in Drosophila melanogaster

Abstract: We observed heteroses for body weight in Drosophila melanogaster after generating hybrids from three inbred lines. To better understand the mechanism for this phenomenon at the mRNA level, we compared the mRNA profiles of the parental and hybrid lines using high-throughput RNA-seq. A total of 5877 differentially expressed genes (DEGs) were found and about 92% of these exhibited parental expression level dominance. Genes in the dominance category were functionally characterized using the Kyoto Encyclopedia of G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 45 publications
1
23
1
Order By: Relevance
“…Therefore, the livers of females obtained at six weeks of age were used for RNA sequencing. A large number of DEGs were identified between reciprocal crosses and parental lines, indicating that heterosis is a consequence of polygenic effects; this was consistent with results given by previous studies [30,31].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, the livers of females obtained at six weeks of age were used for RNA sequencing. A large number of DEGs were identified between reciprocal crosses and parental lines, indicating that heterosis is a consequence of polygenic effects; this was consistent with results given by previous studies [30,31].…”
Section: Discussionsupporting
confidence: 91%
“…A pathway of steroid biosynthesis was significantly enriched in high-parent dominant genes for the RC group. Mu et al [30] reported that steroid biosynthesis gene up-regulation increased fat deposition in ovariectomized chickens. However, in our study, no shared significant KEGG pathway was enriched in the high-parent dominant genes of reciprocal crosses.…”
Section: Discussionmentioning
confidence: 99%
“…Hybrid vigor, or heterosis, refers to the superior performance of hybrid progeny relative to their inbred parents 1 4 . Heterosis in plants of diverse species is associated with many superior agronomic characteristics, including larger plant stature, increased biomass, growth rate, grain yield, and tolerance to abiotic stresses.…”
Section: Introductionmentioning
confidence: 99%
“…Next-generation sequencing (NGS) especially high-throughput RNA sequencing (RNA-seq) technology is advantageously used for discovering heterotic genes over other expression profiling technologies in plants and animals 13,[24][25][26] . In plants, using RNA-Seq technology, expression patterns of DEGs between hybrids and their parents can be analyzed that might contribute to understanding the genetic basis of heterosis 13,27,28 .…”
mentioning
confidence: 99%